Benign Pilomatricoma in a Shih-Tzu Dog - Jorge, Manuela Amanda; Charas dos Santos, Ivan Felismino [UNESP]; Oliveira, Julia Viana de; Maciel de Mendonca, Maria Luiza; Sartori, Mariana; Moretti, Marcela Fernanda; Zacarias, Ademir; Zadra, Vivian Ferreira (Univ Fed Rio Grande Do Sul, 2023)
Background: Pilomatricomas are neoplasms of hair follicles, located in the hair bulb, and the incidence is uncommon in the clinical-surgical clinical routine of dogs and cats. It commonly affects adult animals, with no predisposition to sex or race, and is mainly located in the neck, back, and tail region. The diagnosis is made by histopathological examination, where cells are observed in which their nucleus does not stain with hematoxylin and eosin - empty nucleus. The present work aimed to report a case of benign pilomatricoma since it is a rare condition in dogs and cats and, consequently, there is little information in the literature. Case: A 6-year-old male Shih-Tzu dog, not submitted to surgical contraception, weighing 6.9 kg, was treated at the Veterinary School Hospital (HVE) of the North Parana State University (UENP), Bandeirantes, PR, Brazil, with a history of nodules in the tail region, lasting 6 months. On physical examination, no changes were identified in the patient's physiological parameters. However, the presence of neoformations in the distal and medial region of the tail, similar to a nail, adherent, non-ulcerated and non-alopecic, and absence of pruritus or self-mutilation were identified. Vaccination and deworming were updated. Hematological examination, serum biochemicals (urea, creatinine, alanine aminotransferase, alkaline phosphatase, and albumin), and abdominal ultrasound showed no changes. According to the clinical and laboratory signs, it was decided to perform an excisional biopsy, using a caudectomy, for subsequent histopathological examination. The specimens were fixed in 10% formaldehyde and sent for histopathological examination. Histological examination was compatible with benign pilomatricoma. Postoperatively, cephalexin, dipyrone, tramadol hydrochloride, and meloxicam were prescribed, surgical wound cleaning, and the use of an Elizabethan collar until the suture was removed. After 10 days of the surgical procedure, the patient was asked to remove the sutures, and no changes were identified regarding the physiological parameters and blood count. Discussion: Pilomatricomas are commonly benign neoplasms arising from the germ cells of the follicular matrix. They present dermal or subdermal forms, with several cystic structures which are surrounded by keratinocytes, similar to the matrix cells of an anagen hair follicle, more keratinized and firmer areas, corroborating the results of the present report. In the ultrasound examination, the presence of intra-abdominal metastases was not identified, which is consistent with the literature, since in this type of neoplasm it is not common to identify foci of intra-abdominal and thoracic metastases. In the present report, immunohistochemistry was not used, even though it is used to differentiate follicular neoplasms from pilomatricomas. However, histopathological examination is considered the best method for the definitive diagnosis of pilomatricomas in dogs. It was concluded that the surgical treatment through excisional biopsy, with safety margins of 2 cm, was effective as a therapeutic method in the case of benign pilomatricoma, and the definitive diagnosis must be made through histopathological examination.
Keywords: surgery; dermatology; hair follicle; neoplasia